2022
DOI: 10.1016/j.ijom.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of the epidemiology of oral squamous cell carcinoma in the Netherlands 1989–2018, with emphasis on young adults

Abstract: There has been an increasing trend in oral squamous cell carcinoma (OSCC) in patients under 45 years of age. The aim of this study was to evaluate the burden of OSCC in the Netherlands between 1989 and 2018 among young adults (age 20-34 years) when compared to adults (age 35-44 years), and to describe the burden in older groups as well, utilizing cancer registry data to characterize incidence patterns by age, sex, and risk factors. A total of 18,963 cases of OSCC were reported. The overall incidence rate, as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Second, this study was conducted in a single academic institution in Belgium and thus the results are difficult to generalize worldwide. However, the population of this study was similar to the populations of other studies with patients with head and neck cancer in other countries 9,39 . A multicenter, prospective study could solve both previous limitations of this study.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Second, this study was conducted in a single academic institution in Belgium and thus the results are difficult to generalize worldwide. However, the population of this study was similar to the populations of other studies with patients with head and neck cancer in other countries 9,39 . A multicenter, prospective study could solve both previous limitations of this study.…”
Section: Discussionsupporting
confidence: 53%
“…However, the population of this study was similar to the populations of other studies with patients with head and neck cancer in other countries. 9,39 A multicenter, prospective study could solve both previous limitations of this study. Third, the severity of comorbidities was not taken into consideration in the comorbidity scales evaluated in the present research.…”
Section: Discussionmentioning
confidence: 94%
“…A single-center study on 10 years of cancer registry data more attention to this disease (7). It has been reported that OSCC biological behavior in young patients differs from that in patients with advanced age (8).…”
Section: Clinicopathological Characteristics Predicting Advanced Stag...mentioning
confidence: 99%
“…Evaluation of histological characteristics serves a vital role in diagnosing resected tumor specimens, and efforts have been undertaken to predict clinical outcomes and therapeutic responses using these (6). Numerous studies have reported that parameters involved include size and primary site of the tumor, Tumor-Node-Metastasis (TNM) staging, tumor differentiation and lymphovascular invasion (LVI) (4,(6)(7)(8). Moreover, the increasing frequency of OSCC among young patients in several regions should attract…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), cancer would take the lives of 10.3 million people globally by 2020, and patients with oral cancer would have a five-year survival rate of just 50% globally. Oral cancer is a challenging disease that affects about 600,000 individuals worldwide each year and is linked to a high rate of morbidity and mortality [1][2][3][4]. Mouth cancer is a group of tumors that may affect any area of the mouth, including the pharynx and salivary glands, as well as the surrounding tissues [5].…”
Section: Introductionmentioning
confidence: 99%